Literature Review: Dampak Iklim Global terhadap Fenologi Tanaman - Vanesa Cinta Efandri; Vauzia Vauzia (Institut Agama Islam Negeri Kerinci, 2025)
Climate is one of the most important environmental factors and gets a lot of public attention today. This is because climate has an importance on all aspects of life including health, agriculture, and the economy. Climate has an impact on the physiology and phenology of a plant, thus affecting plant growth and production. Plants will adapt to changes in environmental conditions shown through their phenology. The purpose of writing this literature review is to assess the impact caused by climate on the phenology of various plants. The method used is a literature review based on relevant sources related to the title and sourced from databases such as ScienceDirect, Google Scholar and ResearchGate published from 2014-2024. Based on the results of the literature review, it was found that climate greatly affects plant growth and development. Changes in temperature, humidity, sunlight intensity, and rainfall in a place have caused phenological changes in various plants both in the vegetative phase and the generative phase of the plant.